Assessing a peptidylic inhibitor-based therapeutic approach that simultaneously suppresses polyglutamine RNA- and protein-mediated toxicities in patient cells and Drosophila - Qian Zhang; Ho Tsoi; Shaohong Peng; Pan P. Li; Kwok-Fai Lau; Dobrila D. Rudnicki; Jacky Chi-Ki Ngo; Ho Yin Edwin Chan (The Company of Biologists, 2016)
Polyglutamine (polyQ) diseases represent a group of progressive neurodegenerative disorders that are caused by abnormal expansion of CAG triplet nucleotides in disease genes. Recent evidence indicates that not only mutant polyQ proteins, but also their corresponding mutant RNAs, contribute to the pathogenesis of polyQ diseases. Here, we describe the identification of a 13-amino-acid peptide, P3, which binds directly and preferentially to long-CAG RNA within the pathogenic range. When administered to cell and Drosophila disease models, as well as to patient-derived fibroblasts, P3 inhibited expanded-CAG-RNA-induced nucleolar stress and suppressed neurotoxicity. We further examined the combined therapeutic effect of P3 and polyQ-binding peptide 1 (QBP1), a well-characterized polyQ protein toxicity inhibitor, on neurodegeneration. When P3 and QBP1 were co-administered to disease models, both RNA and protein toxicities were effectively mitigated, resulting in a notable improvement of neurotoxicity suppression compared with the P3 and QBP1 single-treatment controls. Our findings indicate that targeting toxic RNAs and/or simultaneous targeting of toxic RNAs and their corresponding proteins could open up a new therapeutic strategy for treating polyQ degeneration.